ANAESTHETIC MANAGEMENT OF TRACHEOBRONCHIAL FOREIGN BODIES IN CHILDREN - Gilani, Syed Mushtaq; Ghani, Rehman; Nabi, Ghulam (Journal of Ayub Medical College Abbottabad, 1999)
Tracheobronchial foreign bodies in children mostly present as emergency to hospital. Sander's technique is the great advantage for the removed of tracheobronchial foreign bodies by rigid bronchoscope. It has made the procedure safe for removal of foreign bodies in children, particularly for prolonged endoscopy. Preoperative preparation of the patient with the administration of antibiotics, intravenous fluids and steroids has made the endoscopy easier. Safe and suitable general anaesthesia by an experienced anesthesiologist is required for complete removal of tracheobronchial foreign body. In the present study most of the foreign bodies removed from the children were small plastic- whistles available as free gifts with some cheap candies in the local market.